Clinical practice guidelines for endoscopic papillectomy. Issue 3 (21st February 2022) - Itoi, Takao; Ryozawa, Shomei; Katanuma, Akio; Kawashima, Hiroki; Iwasaki, Eisuke; Hashimoto, Shinichi; Yamamoto, Kenjiro; Ueki, Toshiharu; Igarashi, Yoshinori; Inui, Kazuo; Fujita, Naotaka; Fujimoto, Kazuma
Abstract : The Japan Gastroenterological Endoscopy Society has developed the "Clinical Practice Guidelines for Endoscopic Papillectomy (EP)" as a fundamental guideline using scientific approach. EP is a recently spreading therapeutic modality for ampullary tumors ranked as high risk endoscopic technique. Because of the paucity of high level of evidence, strength of recommendations had to be determined by a consensus among specialists. These guidelines, shed light on the following five issues: Indications, Preoperative/intraoperative preparations and techniques, Early adverse events, Therapeutic outcomes and remnants/recurrences, and Follow‐up and late adverse events, to guide current clinical practice on EP.